The Epidemiology of Excess Mortality in People with Mental Illness - Lawrence, David; Kisely, S.; Pais, J. (Canadian Psychiatric Association, 2010)
The epidemiology of excess mortality in people with mental illness.Lawrence D, Kisely S, Pais J.Centre for Developmental Health, Curtin University of Technology and Telethon Institute for Child Health Research, Perth, Australia. D.Laurence@curtin.edu.auComment in: * Can J Psychiatry. 2010 Dec;55(12):749-51. AbstractOBJECTIVE: to investigate the burden of excess mortality among people with mental illness in developed countries, how it is distributed, and whether it has changed over time.METHOD: we conducted a systematic search of MEDLINE, restricting our attention to peer-reviewed studies and reviews published in English relating to mortality and mental illness. Because of the large number of studies that have been undertaken during the last 30 years, we have selected a representative cross-section of studies for inclusion in our review.RESULTS: there is substantial excess mortality in people with mental illness for almost all psychiatric disorders and all main causes of death. Consistently elevated rates have been observed across settings and over time. The highest numbers of excess deaths are due to cardiovascular and respiratory diseases. With life expectancy increasing in the general population, the disparity in mortality outcomes for people with mental illness is increasing.CONCLUSIONS: without the development of alternative approaches to promoting and treating the physical health of people with mental illness, it is possible that the disparity in mortality outcomes will persist.PMID: 21172095 [PubMed - in process]Publication TypesPublication Types: * Research Support, Non-U.S. Gov'tLinkOut - more resources